2001
DOI: 10.1002/em.1019
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity analysis of the potentiation by aminothiols of the chromosome‐damaging effect of bleomycin in G0 human lymphocytes

Abstract: The radioprotective aminothiols 2-[(aminopropyl)amino] ethanethiol (WR-1065) and cysteamine (CSM) potentiate the induction of chromosomal damage by the radiomimetic compound bleomycin (BLM) in G0 human lymphocytes. To investigate the mechanism of potentiation, we measured the clastogenic activity of BLM in the cytokinesis-block micronucleus assay in the presence and absence of amines, thiols, and aminothiols. The hydroxy analog of WR-1065, 2-(3-aminopropylamino) ethanol (WR-OH), potentiates BLM only slightly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…In the case of intercalators, however, the interaction appears to be uniformly one of BLM amplification. The generality of BLM enhancement by intercalators does not preclude other possible means of potentiation, including enhanced BLM activation through redox mechanisms, improved BLM uptake, or altered DNA repair [Hoffmann et al, 1995[Hoffmann et al, , 2001Snyder, 2007].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the case of intercalators, however, the interaction appears to be uniformly one of BLM amplification. The generality of BLM enhancement by intercalators does not preclude other possible means of potentiation, including enhanced BLM activation through redox mechanisms, improved BLM uptake, or altered DNA repair [Hoffmann et al, 1995[Hoffmann et al, , 2001Snyder, 2007].…”
Section: Discussionmentioning
confidence: 95%
“…BLM is a potent mutagen, clastogen, and recombinagen, and earlier studies have shown that its genetic activity can be reduced by antimutagens or enhanced by various agents, including 3-aminobenzamide, aminothiols, caffeine, ethanol, hydroxyurea, isoptin, heterocyclic aromatic intercalating agents, hyperthermia, ß-carotene, triethylenetetramine, and hyperbaric oxygen (reviewed in Hoffmann et al [2001]). Several mechanisms of modulation of BLM have been described in yeast strain D7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, amifostine has also been reported to potentially compromise anticancer therapies. Previous research has indicated that amifostine impaired p53-induced apoptosis in myeloid leukemia cells (17) and potentiated bleomycin-induced DNA damage in human lymphocytes (27). Pretreatment with Figure 6.…”
Section: Discussionmentioning
confidence: 83%